A H2O2-responsive theranostic platform for chemiluminescence detection and synergistic therapy of tumors. Issue 10 (23rd February 2022) - Yu, Yun; Xie, Bo-Ru; Liu, Xin-Hua; Ye, Jing-Jie; Cheng, Han; Zhong, Zhenlin; Zhang, Xian-Zheng
Abstract : A theranostic nanosystem L-HPOX presented H2 O2 -responsive chemiluminescence and drug delivery abilities. By combination with DMXAA, L-HPOX demonstrated good capabilities of tumor imaging and treatment due to the increased H2 O2 at the tumor site. Abstract : Chemiluminescence substances that respond to hydrogen peroxide (H2 O2 ) in a tumor microenvironment have the potential to achieve accurate tumor imaging. Here, Pluronic F-127 (PF127) and polymers containing oxalate ester (POE) were assembled by hydrophilic and hydrophobic forces to form nanoparticles to load the anti-tumor drug lapachone (Lapa) and rubrene. The Lapa-loaded H2 O2 -responsive nanoparticles (L-HPOX) could track tumors in vivo through H2 O2 -related chemiluminescence. With the presence of H2 O2 in the tumor microenvironment, L-HPOX would collapse and release the loaded drug for anti-tumor therapy. After treatment with 5, 6-dimethylxanthenone-4-acetic acid (DMXAA), the inflammatory level and H2 O2 content increased. Thus, L-HPOX exhibited good capabilities of tumor imaging and treatment. Importantly, the immune system was also activated for anti-metastatic activity. This intelligent and efficient chemiluminescent tumor theranostic nanoplatform will find great potential for precise and efficient tumor treatment.